Analysis of acrylamide in drinking water by SPE and GC–MS - Hale Seçilmiş Canbay; Mahmut Doğantürk (Applied Water Science, 2019)
Abstract The present study aimed to evaluate the levels of acrylamide in drinking water by solid phase extraction (SPE). After SPE, water extracts were analyzed using gas chromatography–mass spectrometry (GC–MS) system. Thirty drinking water samples were analyzed in the study. Acrylamide was detected in 12 samples. The levels of acrylamide in drinking water samples were less than 85 ng l−1. The limit of detection and limit of quantification were 4 and 13.20 ng l−1, respectively.